Analisis pasar dalam pengembangan produk buku cerita bergambar di anak sekolah dasar - Bahriyah, Baridatul; Nadia, Nadia; Fathullah, M Farid; Abdillah, M Wildan; Zuhriyah, Indah Aminatuz (Maliki Interdisciplinary Journal, 2024)
Market analysis is the study of a particular market within an industry, including an examination of its various components, such as market size, key success factors, distribution channels, target audience, profitability and growth rates, and market trends. The characteristics of students aged 7 - 11 years are classified into the concrete operational stage. At this age, which are still considered children, they prefer learning resources that attract students' attention and interest in learning. Picture story books are very popular with all students at the elementary school level. For this reason, picture story books can be used to be developed as supporting resources in elementary schools. This research aims to produce valid and practical learning resources in elementary schools in class I. This research is research and development with the ADDIE development model, namely Analysis, Design (Planning), Development (Development), Implementations (Trial) and Evaluation (Evaluation) with research subjects of class I students at SD Negeri 2 Madiredo and MI Raden Fatah Pujon. The validity of learning sources is obtained through learning validation. Meanwhile, the practicality of learning resources is obtained from teacher and student response questionnaires. The results obtained in the practicality of picture story books from teacher responses obtained a value of 4.75 with a very valid category, student responses with a percentage of 4.6 with a very valid category. Based on the results obtained, it can be concluded that the development of picture story books for elementary school students is included in the very valid and very practical category for use in the learning process. In this way, picture story books can be tested in class I elementary schools